Pengembangan Potensi Ekonomi Masyarakat Desa Kwala Serapuh: Pendekatan Berbasis Pemberdayaan Ekonomi - Maya Macia Sari; Eli Delvi Yanti; Rizco Rama Doni (Journal of Social Responsibility Projects by Higher Education Forum, 2023)
Local economic empowerment is one of the efforts to improve the economy of rural communities. Community service activities have been carried out on August 1, 2023 in Kwala Sefragile Village, Langkat, North Sumatra Province. This service was carried out by a service team from Universitas Pembangunan Panca Budi Medan consisting of lecturers and students in the Management Study Program. The purpose of this service is to improve the economy of the people of Kwala Sefragile Village through the development of local economic potential. The potential of the local economy developed is the potential of agriculture, plantations, and tourism. This service activity is divided into three stages, namely: 1) Preparatory stage, 2) Implementation stage and 3) Evaluation stage. Based on the results of this service, it can be concluded that an approach based on local economic empowerment can have a positive impact on the economy of rural communities. The community has new skills and knowledge to develop local economic potential. In addition, the community also has access to support from the private sector and the government.